Mobile Robot for Fires Detection Development (Journal of Universal Science Research, 2023)
In the article, the authors propose the development of a mobile robot. The base is Arduino Mega 2560 R3. The wheelbase chosen is a single-deck robot platform. Breadboard without ration MB-102 with 400 points was selected next. The robot is equipped with the following sensors: ultrasonic sensor HC-SR04, KY-033 Line sensor, flame sensor KY-026, IR thermomodule, Wi-Fi module ESP8266 version ESP-01. The rest of the article suggests programming the fire sensor.